Exploring the Impostor Phenomenon Among Korean Daycare Directors: A Grounded Theory Approach - Ji-Hyeon Choi; Young-Eun Lee (Behavioral Sciences)
The impostor phenomenon, characterized by self-doubt and an external attribution of success, significantly impacts daycare center directors, influencing their leadership effectiveness and childcare quality. This qualitative study aims to explore how the impostor phenomenon manifests among Korean daycare center directors within an ecological framework. Semi-structured interviews were conducted with 15 Korean daycare center directors using grounded theory methods. Analysis identified the phenomenon across cognitive, emotional, and behavioral dimensions, revealing both negative self-perceptions and strategic, perfectionism-related behaviors consistent with previous research. This study proposes a contextual model based on Bronfenbrenner’s ecological systems theory, illustrating interactions at macrosystem, exosystem, mesosystem, microsystem, and chronosystem levels, with a detailed paradigm model further explaining microsystem and chronosystem interactions. These findings contribute to clarifying and contextualizing the impostor phenomenon, particularly highlighting situational influences and strategic manifestations. This research provides a foundation for future studies in South Korean contexts and practical insights for developing targeted leadership support programs for daycare center directors.